2011
DOI: 10.1007/s11434-011-4397-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfide on sulfate reducing bacteria in response to Cu(II), Hg(II) and Cr(VI) toxicity

Abstract: Sulfate reducing bacteria (SRB) is identified as the primary organisms responsible for the treatment of heavy metal wastewater. However, most heavy metals can inhibit the growth of SRB during heavy metal treatment processes. Sulfide is a metabolic product of SRB and it can precipitate or reduce heavy metals. This study focused on the effects of sulfide on SRB resistance to Cu(II), Hg(I) and Cr(VI) toxicity. First, we considered the existence style of various heavy metals with and without sulfide addition by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Bioprecipitation of copper as well as sulphate reduction occurred maximally at lower concentrations of metal (1 and 5 ppm) and decreased retrogressively as the concentration of the dissolved metal increased (from 10 to 15 ppm). These results were in accordance with the data reported previously (Sani et al 2001 ; Utgikar et al 2003 ; Cabrera et al 2006 ; Azabou et al 2007 ; Sheng et al 2011 ). Various researchers have proved the stimulatory effects of heavy metals on SRB at lower concentrations and inhibitory (causing a reduction of metabolic activity) or even toxic (causing death) at higher concentrations (Utgikar et al 2002 ; Sani et al 2003 ).…”
Section: Discussionsupporting
confidence: 93%
“…Bioprecipitation of copper as well as sulphate reduction occurred maximally at lower concentrations of metal (1 and 5 ppm) and decreased retrogressively as the concentration of the dissolved metal increased (from 10 to 15 ppm). These results were in accordance with the data reported previously (Sani et al 2001 ; Utgikar et al 2003 ; Cabrera et al 2006 ; Azabou et al 2007 ; Sheng et al 2011 ). Various researchers have proved the stimulatory effects of heavy metals on SRB at lower concentrations and inhibitory (causing a reduction of metabolic activity) or even toxic (causing death) at higher concentrations (Utgikar et al 2002 ; Sani et al 2003 ).…”
Section: Discussionsupporting
confidence: 93%
“…2). Sheng et al (2011) found similar patterns, when the initial concentration of Cu was higher than 0.3 mM, the sulfate concentration barely changed during the experiment, which indicates that SRB activity was completely inhibited. In the study of Guo et al (2017b), when the concentrations of Zn −2 were below 0.2 mM, the sulfate reduction efficiency was greater than 95.2%, when Zn −2 concentration was increased to 1.5 mM, the efficiency decreased to 10%.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the high binding capacity of metallothionein is that it is rich in thiol groups. The thiol group has higher binding ability to metal than the amino group and the carboxyl group [112]. CUP1 is a metallothionein found in S. cerevisiae, which has been shown to protect yeast cells against oxidants [113].…”
Section: Metallothionein and Phytochelinmentioning
confidence: 99%